Mean Duration for Cessation of Pain following Tonsillectomy Operation among the Patients of Otolaryngology Department in a Tertiary Care Hospital: A Descriptive Cross-sectional Study - Nain Bahadur Mahato (Nepal Medical Association, 2021)
Introduction: Tonsillectomy is one of the most common surgical procedures performed by Otolaryngologists world-wide. There are various techniques for tonsillectomy, but none of the techniques has been accepted as the best one universally. Despite the efforts of all the surgeon and use of recent techniques, some post-tonsillectomy morbidity is unavoidable. The main objective of our study is to find out the mean duration for cessation of pain among the patients following tonsillectomy operation in a tertiary care hospital.